Solve : 6-3(2x - 3) = 5 (6-x) - 4x
'
Attachments:
![](https://hi-static.z-dn.net/files/d85/f848a272fa6c953c63ad0eeab5be0f97.jpg)
Answers
Answered by
9
Step-by-step explanation:
6 - 6x - 9 = 30 - 5x - 4x
6 - 9 - 30 = 6x - 5x - 4x
6 - 39 = -3x
-33 = 3x
-33 / 3 = x
-11 = x
x = -11
Hope it helps you...Mark me as Brainiest...
Thank uh...♥️
Answered by
1
Answer:
hzbz znznsnznz sndn x dn
Step-by-step explanation:
nxnznxnxjd x nx x xjsnd x.
Similar questions
India Languages,
4 months ago
French,
4 months ago
Psychology,
4 months ago
Biology,
8 months ago
Math,
8 months ago
Social Sciences,
1 year ago
Math,
1 year ago
English,
1 year ago